Initial experience of intraoperative radiotherapy as tumour bed boost after neoadjuvant chemotherapy in breast cancer patients - Spaich, Saskia; Tuschy, Benjamin; Sperk, Elena; Wenz, Frederik; Sütterlin, Marc (Translational cancer research, 2017)
Background: Radiotherapy has shown high efficacy in breast cancer therapy; in recent years, benefits of its intraoperative application were demonstrated. The aim of our study is to report initial experience of intraoperative radiotherapy (IORT) during breast conserving surgery (BCS) followed by external beam whole breast radiotherapy (EBRT) in patients with breast cancer after completion of neoadjuvant chemotherapy (nCHT). Methods: We retrospectively analysed data of 13 consecutive women who had completed nCHT because of locally advanced breast cancer and subsequently underwent IORT during BCS between 2005 and 2012. Demographic, clinical/surgical and histological parameters were evaluated and follow-up assessment was performed (median follow-up: 37 months, range 3-41 months). Results: Thirteen women (one with bilateral malignancy) received nCHT followed by BCS with IORT. The most frequent acute side effect was erythema (GI/II), occurring in 4 cases (4/14; 29%). Late follow-up analysis could be performed in 10 patients (median FU 40 months, range 31-41 months). Six of these patients (6/10, 60%) presented with low/moderate tumour bed fibrosis. No grade III fibrosis was observed. Three patients (3/10, 30%) had developed skin retractions. Five patients (5/10, 50%) complained about pain during late follow-up. There was no case of severe toxicity after IORT treatment up to the time of final evaluation. Conclusions: No relevant increase in severe acute and late complications could be observed in this small group of breast cancer patients who had received a combination of IORT and BCS followed by EBRT after completion of nCHT. This pilot study raises hope that IORT and BCS may be a feasible and safe enhancement of treatment strategies in this subgroup of patients with locally advanced malignancy.